LCA data quality: A management science perspective. (10th July 2017) - Bicalho, Tereza; Sauer, Ildo; Rambaud, Alexandre; Altukhova, Yulia
Abstract: Companies represent essential sources of data for Life Cycle Assessment (LCA). However, management systems and management approaches are rarely informed by LCA data developments, and vice-versa. The present paper focuses on the role of the company in the LCA data collection process. The objective is to investigate the adequacy of the current LCA data quality assessment approach from a management perspective. This is accomplished by applying the ecoinvent Data Quality System (DQS) to a primary LCA data collection project, including an immersion within the organisation and taking subjective experiences into account during the data collection process. Our analysis relies on two theoretical fields in management sciences: first, management tools and second, environmental accounting. The study demonstrates that the current prevailing LCA data quality assessment approach is inadequate for enterprise-specific data because it focuses uniquely on industry average data. The study also indicates that LCA constitutes a passive user-based tool. Hence, the drawbacks related to data management and control within the organisation are completely neglected in LCA developments. Finally, our analysis provides concrete suggestions for allowing consistent data quality assessment that would ensure the usefulness of LCA information. Highlights: From a management perspective, LCA constitutes a passive user-based tool. The current prevailing LCA approach of data quality assessment is inadequate for enterprise-specific data. Concrete suggestions for consistent LCA data quality assessment are provided.